Pelatihan Pemanfaatan Gimkit sebagai Media Pembelajaran Berbasis Game Bagi Guru Sekolah Menengah - Andi Citra Pratiwi; Firdaus Daud; A. Mushawwir Taiyeb; Ismail; Muhammad Junda; Nur Intan Marzuki (Jurusan Matematika FMIPA UNM, 2024)
The proper utilization of educational media is crucial for the effectiveness and efficiency of learning. Given the characteristics of Generation Z and Alpha, who are familiar with digital technology, it is important for teachers to integrate engaging digital learning media. Issues such as low motivation and student engagement are often caused by inappropriate learning media. Using game-based learning applications like Gimkit can be an effective solution. Gimkit allows teachers to provide practice questions in a fun game format, enhancing student understanding. However, in Majene Regency, the use of Gimkit is not widely known among teachers. Therefore, a training session was held to introduce and train 25 secondary school teachers in Majene Regency on May 11, 2024, at SMPN 2 Majene, West Sulawesi. This training employed lecture and practical methods, including presentations on gamification in education, types of gamification applications, and the use of Gimkit. Participants practiced creating accounts, making question sets (Kits), and simulating games with Gimkit, followed by discussions on suitable materials for this application. Questionnaires indicated that the training met the participants' needs, was clearly presented, and was beneficial in increasing their knowledge of game-based learning media. This training is expected to improve student motivation and engagement in learning in Majene Regency